Implementation of Parent Company's Liability for Bankruptcy Experienced by Subsidiary: Case in Indonesia - Annurdi; Santoso, Budi; Widhiyanti, Hanif Nur; Dewantara, Reka (Journal of Finance and Financial Law, 2024)
The purpose of the article. The article aims to reveal the existence of vacuum of norms regarding a group company in Indonesia, especially regarding the parent company's responsibility for bankruptcy experienced by its subsidiary.Methodology. This research is normative juridical research. It uses several approaches to obtain information from various aspects regarding the legal issues being studied, namely the statute approach and case approach.Results of the research. This legal vacuum causes differences of opinions among judges in assessing the relationship between a parent company and its subsidiary as a basis for implementing the parent company's liability for bankruptcy experienced by its subsidiaries. In this research, there were cases where the judge found that the parent company was not responsible for the losses or bankruptcy experienced by its subsidiary on the basis that these two companies were separate entities. Meanwhile, in a different case, a judge's opinion was that the parent company and its subsidiary were a single economic entity and there was a special relationship between the two companies, so that the parent company was liable for the bankruptcy experienced by its subsidiary. In this regard, we are of the opinion that it is necessary to establish legislation regarding a group company, specifically regulating the liability of parent company for bankruptcy experienced by its subsidiary in order to guarantee legal certainty and provide legal protection for all relevant stakeholders.